Do Brazilian scientific journals promote the adherence of Chagas disease researchers to internacional ethical principals? - Malafaia, Guilherme; Guilhem, Dirce; Talvani, André (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
The ethical aspects of the Brazilian publications about human Chagas disease (CD) developed between 1996 and 2010 and the policy adopted by Brazilian medical journals were analyzed. Articles were selected on the SciELO Brazil data basis, and the evaluation of ethical aspects was based on the normative contents about ethics in research involving human experimentation according to the Brazilian resolution of the National Health Council no. 196/1996. The editorial policies of the section "Instructions to authors" were analyzed. In the period of 1996-2012, 58.9% of articles involving human Chagas disease did not refer to the fulfillment of the ethical aspects concerning research with human beings. In 80% of the journals, the requirements and confirmation of the information about ethical aspects in the studies of human CD were not observed. Although a failure in this type of service is still observed, awareness has been raised in federal agencies, educational institutions/research and publishing groups to standardize the procedures and ethical requirements for the Brazilian journals, reinforcing the fulfillment of the ethical parameters, according to the resolution of NHC no. 196/1996.